The Polemic with the Metaphysical Addressee in Contemporary Lithuanian Essays - Čiočytė, Dalia (Literatūra, 2018)
[article in Lithuanian; only abstract in English] This article investigates the notion of the metaphysical and its influence on the narrator’s consciousness in contemporary Lithuanian essays. The theoretical perspective combines the theology of literature with Mikhail Bakhtin’s concept of the hidden polemic. The polemic of the narrator with the metaphysical addressee is being analyzed in three representative texts of the contemporary essay: Offering by Sigitas Parulskis (2002), The Allure of the Text by Giedra Radvilavičiūtė (2010) and Farewell to Things by Alfonsas Andriuškevičius (2015). These literary works present an artistic deautomatization of the main existential questions. The literary thought seen in the Offering is an ontological one, as it explains the metaphysical logic of human existence. The literary thought observed in The Allure of the Text and Farewell to Things is a gnoseological quest for the answers to the main questions of human existence.